Analysis of possibilities qualimetric approach for marine conservation operating parameters bearings - Куриляк, Валентина Василівна; Хімічева, Ганна Іванівна (Eastern-European Journal of Enterprise Technologies, 2015)
The applicability of the qualimetric approach for evaluating the maintenance quality of journaland-thrust plain and rolling bearings of the ship shafting system was substantiated. Existing methods of technical monitoring of bearings were analyzed and their main weaknesses were shown. Using the controlmaintenance charts, containing the data collected during the operation of bearing units was proposed for preserving the service life of bearings. The analysis has shown that the technical state evaluation of bearings is relevant because the presence of sensory and expert methods in the maintenance of bearings is insufficient and needs deeper study. Since a positive solution to the problem of poor maintenance of ship bearings will allow to operate bearings during the specified life, prevent premature destruction of the bearing components, and increase the reliability and accuracy of information about the real state of the bearing unit in operation. A detailed analysis of existing methods of technical maintenance control of bearing units has confirmed that there are shortcomings that reduce the actual life of ship shafting bearings. Also, studies have shown that there is an urgent need to modernize sensory and expert approach for evaluating maintenance quality of bearing units. In the research, existing methods for evaluating the maintenance quality of bearings were improved through modernization and addition. This has allowed the updated method for assessing the state of bearings to collect, store and develop technical reports on the experience in the maintenance of bearing units. The purpose of it was to prevent the premature destruction of the bearing unit parts and the availability of qualified maintenance based on the experience gained. Thus, the analysis has shown and proved that the applicability of the modernized expert approach for assessing the maintenance quality of bearings is a rational solution to the existing problem, namely the incomplete life utilization of thrust bearing units.